2 - ELBA ISLAND - C - WESTERN ELBA - Coli, Massimo; Conticelli, Sandro; Pandeli, Enrico; Moratti, Giovanna; Papini, Paola; Tommasini, Simone (Ofioliti, 2007)
This part of the field trip (Fig. 1) is devoted to observe the main geological feature of western Elba: i- Mt. Capanne intrusion, a monzogranitic magmatic body with associate dike swarms and microgranite masses and, ii- its thermometamorphic aureole consisting of several types of hornfels after the ophiolite succession.